Pelatihan Pembuatan Foto Esai Sejarah Budaya Bagi Komunitas Pelajar Sejarah (KOPAJA) SMA Tugu Malang - Wijaya, Daya Negeri; Wahyudi, Deny Yudo; Nafi’ah, Ulfatun; Nagari, Primasa Minerva (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2024)
Purpose – This study aims to develop students' ability to understand and document cultural history through photo essay-making training for Komunitas Pelajar Sejarah (KOPAJA) SMA Tugu Malang Design/methodology/approach –This activity had three stages consisting planning, implementation, and evaluation. Planning was designed to ensure the activity could be run smoothly. Activity implementation comprised of theory sessions (material delivery and discussion), field practice (walking tour), and editing sessions (composing photo essays in groups). Findings –The finding shows a significant improvement in the participants' photography skills and visual narrative ability, as well as an increased appreciation of the cultural history of the colonial period. Participants are expected to be at the forefront of tourism. They are expected to open new jobs in tourism Originality/value – The originality of this activity lies in the interdisciplinary approach that combines elements of history and visual arts, which not only enriches history learning methods in schools but also inspires students to explore and document their cultural heritage. The training successfully demonstrated that using photo essays as a learning tool effectively increases students' understanding and interest in cultural history.